2004
DOI: 10.1108/01443330410790795
|View full text |Cite
|
Sign up to set email alerts
|

Organisational culture and work‐life conflict in the UK

Abstract: This article employs linear regression techniques to model the variables associated with work-life balance outcomes of employees. Using data from employee surveys carried out in four financial sector companies in Scotland, it was found that while the level of perceived availability did not have an impact on work-life balance, organisational culture was significantly associated. This indicates that without a supportive work-life organisational culture, the provision of arrangements in themselves will not necess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 34 publications
(41 reference statements)
3
46
0
Order By: Relevance
“…The census questionnaire collected data on personal and work characteristics, including working status, work patterns and intentions to quit. A measurement scale previously validated for use with workers in a range of settings to measure work/life balance was also included in the questionnaire . The scale consists of 10 statements relating to different aspects of work/life balance, and offers three possible response options.…”
Section: Methodsmentioning
confidence: 99%
“…The census questionnaire collected data on personal and work characteristics, including working status, work patterns and intentions to quit. A measurement scale previously validated for use with workers in a range of settings to measure work/life balance was also included in the questionnaire . The scale consists of 10 statements relating to different aspects of work/life balance, and offers three possible response options.…”
Section: Methodsmentioning
confidence: 99%
“…Bond (2004) found that unsupportive organisational culture promotes WLC among UK employees in the financial sector. Previous studies indicate that organisational culture is a critical factor for achieving WLB (Lewis, 1997;Lewis, 2001;Thompson et al, 1999).…”
Section: Understanding Organisational Culturementioning
confidence: 98%
“…As declared by Fagan and Press, 'parenting and paid work demands continue to challenge ... families in the 21 st century, [and] researchers are increasingly interested in studying the intersection of work and family ' (2008, p. 1136). There is an array of publications detailing the dynamics between work and family life across a diverse range of themes and classifications, such as the economy (Fleetwood, 2007;McDowell, 2004;Perrons, 2003); employment (Berman, 2002;Byrne, 2005;Cohen et al, 2009); the family (Caproni, 2004;Greenhaus and Powell, 2003;Hill et al, 2001;Tausig and Fenwick, 2001); human resources (Felstead et al, 2002;Hyman and Summers, 2004;Lockwood, 2003); sociology (Bond, 2004;Campbell Clark, 2000Warren, 2004) and women (Doherty, 2004;Drew and Murtagh, 2005;Smithson and Stokoe, 2005). Similarly, flexible working practices have also been thoroughly considered in relation to work organization (Gittleman et al, 1998;Pil and Macduffie, 1996;Smith, 1997); techniques (Kathuria and Partovi, 1999;Kalleberg, 2000;Osterman, 1994); trade unions (Croucher and Brewster, 1998;McNabb and Whitfield, 1997;Mueller, 1992) and family life (Lu et al, 2008;Papalexandris and Kramar, 1997;Staines and Pleck, 1986).…”
Section: The Working Fathers' Literaturementioning
confidence: 99%